Weekly external load distribution in football teams of different competitive levels - Coutinho, Diogo; Oliveira, Diogo; Lisboa, Pedro; Campos, Fábio; Nakamura, Fábio Yuzo; Baptista, Jorge; Abade, Eduardo (Biology of Sport, 2024)
This study aimed to compare the microcycle load distribution between teams from different competitive levels. A total of 22 microcycles from one team of each competitive level (first division, 1 st DIV, n = 32 players; second division, 2 nd DIV, n = 23 players; third division, 3 rd DIV, n = 23 players) were monitored using GPS (10 Hz, Catapult). During the match, a higher number of high accelerations (i.e., > 3 m/s, per min) were found in the 3 rd DIV team compared to the 1 st and 2 nd DIV teams. On match day (MD) +1&+2, the 1 st DIV team covered more total (per min, p < 0.001) and high-speed running distance (HSR per min, p < 0.001 and p = 0.042, respectively) than both the 2 nd and 3 rd DIV teams. The 2 nd DIV team showed lower values in most distance-related variables (total distance covered per min, p < 0.001; running distance per min, p < 0.001; HSR per min, p < 0.001; and sprinting distance per min, p < 0.001) for both MD-4 and MD-3 compared to the 1 st and 3 rd DIV teams. In contrast, it showed higher sprinting distance per min ( p < 0.001) on MD-2. In general, the 3 rd DIV team showed higher values in the number of high accelerations (per min, p < 0.001) across all sessions. These results suggest that distance-related variables may be a priority when planning microcycles for the 1 st DIV team, while accelerations are relevant for the 3 rd DIV team. A higher emphasis on external load during MD-2 by the 2 nd DIV team may explain the lower external loads across the microcycle